Effects of Radio Frequency Electromagnetic Fields on the Nervous System. In vitro Experiments (Review) - Natalia I. Khorseva; Pavel E. Grigoriev (Northern (Arctic) Federal University, 2024)
The effects of mobile communications on the population, primarily on children and adolescents as the cohort most vulnerable to any environmental factors, dictates the need for a thorough investigation into the impact of radio frequency electromagnetic fields (RF EMF) on the central nervous system (CNS) as the main target of their action. In this regard, the analysis of experimental data as an indirect assessment of possible negative changes in the body of young animals under the influence of RF EMF, including 5G and Wi-Fi, is highly relevant. We performed a systematization of experimental data, which will be presented in two parts: in vitro and in vivo experiments. This article introduces materials indicating both diversity of approaches to studying the effects of RF EMF on the central nervous system and difficulties of systematizing the results of the experiments. The analysis of literature data showed that, despite the numerous studies into the effects of RF EMF in vitro, CNS cell cultures are used rather rarely. However, this paper examines in detail the results of in vitro experiments: changes in the action potential, morphological changes in cells and the myelin sheath, and changes in the permeability of the blood-brain barrier (using cultures of only nerve cells). It was established that, despite some inconsistency in the results obtained, most studies indicate a negative effect of RF EMF on CNS cells. The morphological and histological changes in CNS structures under the influence of RF EMF will be presented in the next part of the review.